Knowledge and Attitude of Preschool Children Parents Towards Professional Topical Fluoride Therapy - Taravati, Shirin; Lak, Negin (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Purpose: Since various factors such as parents’ attitudes and knowledge can affect the use of fluoride, this study aims to assess the relationship between children’s parents’ attitudes and knowledge towards preventive caries methods with their children’s caries experience. Materials and Methods: In this cross-sectional study, 110 parents of preschool children in Ahvaz were randomly selected. Using a questionnaire, parents’ knowledge and attitude about fluoride therapy were evaluated, and their children’s teeth were examined for dmft. Data were analyzed by Mann-Whitney and Kruskal-Wallis tests. Results: The mean of parents’ knowledge about caries prevention methods was 2.22 ±3.23 of 9, and the knowledge of 68% was poor, 21% moderate, and 11% was good. The mean of parents’ attitude about caries prevention techniques was 9.5±2.05 of 14, and the attitude of 0% was poor,60% moderate, and 40% was good. There was no significant relationship between parents’ knowledge with gender, age, education, source of information, and dmft. There was a direct relationship between knowledge and the experience of professional topical fluoride (PTF). There was no significant relationship between the attitudes of parents with gender, the history of PTF, and the source of information. There was a direct, significant relationship between parents’ attitude and their educational level, age, and child’s dmft. Children’s experience of PTF was 18.6%. Conclusion: Parents’ knowledge and attitude towards fluoride roles in the prevention of dental caries were low. So, assigning programs to increase parents’ knowledge and, subsequently, using caries prevention techniques is suggested.